Mo (CO)6‐assisted Pd‐supported magnetic graphene oxide‐catalyzed carbonylation‐cyclization as an efficient way for the synthesis of 4(3H)‐quinazolinones. (7th February 2019) - Bahadorikhalili, Saeed; Ansari, Samira; Hamedifar, Haleh; Ma'mani, Leila; Babaei, Mohsen; Eqra, Rahim; Mahdavi, Mohammad
Abstract : In this paper, a novel catalyst is introduced based on the immobilization of palladium on modified magnetic graphene oxide nanoparticles. The catalyst is characterized by several methods, including transmission electron microscopy, scanning electron microscopy, X‐ray fluorescence, vibrating‐sample magnetometer, Fourier transform‐infrared and dynamic light scattering (DLS) analysis. The activity of the catalyst was investigated in the synthesis of 4(3 H )‐quinazolinones via Pd‐catalyzed carbonylation‐cyclization of N ‐(2‐bromoaryl) benzimidamides by Mo (CO)6 . The Mo (CO)6 is used as a carbon monoxide source for performing the reaction under mild conditions. The catalyst showed good reusability, and no change in activity was observed after 10 cycles of recovery. Abstract : A novel catalyst is designed and synthesized based on the immobilization of palladium on modified magnetic graphene oxide nanoparticles. For this purpose, magnetic graphene oxide was modified by dendrimer structures, prepared by triazine. The catalyst was used in the synthesis of 4(3 H )‐quinazolinones via Pd‐catalyzed carbonylation‐cyclization of N ‐(2‐bromoaryl) benzimidamides by Mo (CO)6, while the Mo (CO)6 generates carbon monoxide under mild conditions, and this is reported.